Rabbi Nachman’s Sonic Schemes - Shelleg, Assaf (Religions, 2024)
This article discusses Tzvi Avni’s Second Piano Sonata, Epitaph, a sonic commentary on one of the inner tales in Rabbi Nachman’s “The Seven Beggars”. Written between 1974 and 1979, Epitaph not only marks the composer’s act of translation (from words into music and from a textual tale into a wordless and semantically unmarked piano sonata) but also his very turn to ethnographic sources that defied their negative function in a national territorial culture that vilified otherness while separating art from ethnography. Avni’s turn to Rabbi Nachman was part of a bigger shift that saw composers’ dialectical returns to Jewish histories and cultures that were previously repressed from a national culture which dehistoricized the Diaspora to the point of rendering the times and cultures of diasporic Jews a single temporality—ahistorical, contextless, and outside the teleological time of Zionism. With the (re)introduction of diasporic temporalities, non-redemptive poetics became an affordance in the music of Avni or Andre Hajdu (who is also discussed here) while steadily muting the territorial tropes that constituted Hebrew culture.